The Revelation of Reason: Max Weber and Franz Rosenzweig (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The point of departure is how both of the authors criticize Hegel and leave philosophy of history. The exhaustion of Hegel’s historical ontotheology set the task of searching for new ways to deal with history beyond panlogistic identification between reality and concept. So emerged an empiricism of history, which was opened to receive a posteriori the facts of the process of rationalization. Great attention was paid to what set reason in motion from outside itself. It wasn’t possible from a mere historical point of view, but only through the passage to metahistoricity. Its tensions with historicity gave them sufficient grounds to focuse their studies on judaism.